2010
DOI: 10.1186/1476-4598-9-121
|View full text |Cite
|
Sign up to set email alerts
|

Activation of HER family members in gastric carcinoma cells mediates resistance to MET inhibition

Abstract: BackgroundGastric cancer is the second leading cause of cancer mortality in the world. The receptor tyrosine kinase MET is constitutively activated in many gastric cancers and its expression is strictly required for survival of some gastric cancer cells. Thus, MET is considered a good candidate for targeted therapeutic intervention in this type of tumor, and MET inhibitors recently entered clinical trials. One of the major problems of therapies targeting tyrosine kinases is that many tumors are not responsive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 46 publications
(59 reference statements)
0
82
1
Order By: Relevance
“…In MET-addicted gastric cancer, activation of HER family members was poorly responsive to MET inhibitor [29]. In HER2-overexpressing breast cancer, the insulin-like growth factor receptor, other human epidermal growth factor receptor family members (EGFR, HER3) and MET overexpression might be critical for treatmentacquired resistance to trastuzumab [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…In MET-addicted gastric cancer, activation of HER family members was poorly responsive to MET inhibitor [29]. In HER2-overexpressing breast cancer, the insulin-like growth factor receptor, other human epidermal growth factor receptor family members (EGFR, HER3) and MET overexpression might be critical for treatmentacquired resistance to trastuzumab [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…For example, MET amplification or activation is a mechanism of resistance to EGFR inhibition in both NSCLC and colorectal carcinomas (7,22). Conversely, in MET-addicted gastric carcinomas, activation of the ERBB receptors EGFR and ERBB3 maintains resistance to MET inhibition (23). There is a gap in knowledge of the relationship and interactions between MET and the ERBB receptor family in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…ERBB2 þ breast cancers (26,27), and have been shown to play a role in trastuzumab resistance (28,29). In addition, EGFR and ERBB3 can promote the resistance of METaddicted gastric carcinomas to MET inhibitors (23). Therefore, EGFR and ERBB3 are suspects in driving the resistance to ERBB2 or MET knockdown.…”
Section: Met and Erbb2 Compensate For Each Other During Targeted Knocmentioning
confidence: 99%
“…Recent clinical trials have been designed with molecular alterations of cMET, EGFR/RAS/RAF as biomarkers (56,61,84). Future clinical trials may also assess molecular derangements such as cMET mutation, K-ras amplification, EGFR and HER2 status as predictive markers (14,15,83,84,86).…”
Section: Resultsmentioning
confidence: 99%
“…An in vitro and in vivo study indicated that gastric cancer tumors bearing constitutive activation of HER family members responded poorly to MET inhibition (83). cMET activation may mediate resistance to EGFR and HER2 in gastric cancer (14,15).…”
Section: Resistance To Cmet Inhibitorsmentioning
confidence: 99%